A roadmap for sole Cherenkov radiators with SiPMs in TOF-PET. (21st September 2021) - Kratochwil, Nicolaus; Gundacker, Stefan; Auffray, Etiennette
Abstract: Time of flight positron emission tomography can strongly benefit from a very accurate time estimator given by Cherenkov radiation, which is produced upon a 511 keV positron–electron annihilation gamma interaction in heavy inorganic scintillators. While time resolution in the order of 30 ps full width at half maximum (FWHM) has been reported using MCP-PMTs and black painted Cherenkov radiators, such solutions have several disadvantages, like high cost and low detection efficiency of nowadays available MCP-PMTs. On the other hand, silicon photomultipliers (SiPMs) are not limited by those obstacles and provide high photon detection efficiency with a decent time response. Timing performance of PbF2 crystals of various lengths and surface conditions coupled to SiPMs was evaluated against a reference detector with an optimized test setup using high-frequency readout and novel time walk correction, with special attention on the intrinsic limits for one detected Cherenkov photon only. The average number of detected Cherenkov photons largely depends on the crystal surface state, resulting in a tradeoff between low photon time spread, thus good timing performance, and sensitivity. An intrinsic Cherenkov photon yield of 16.5 ± 3.3 was calculated for 2 × 2 × 3 mm 3 sized PbF2 crystals upon 511 keV γ -deposition. After time walk correction based on the slew rate of the signal, assuming two identical detector arms in coincidence, and using all events, a time resolution of 215 ps FWHM (142 ps FWHM) was obtained for 2 × 2 × 20 mm 3 (2 × 2 × 3 mm 3 ) sized PbF2 crystals, compared to 261 ps (190 ps) without correction. Selecting on one detected photon only, a single photon coincidence time resolution of 113 ps FWHM for black painted and 166 ps for Teflon wrapped crystals was measured for 3 mm length, compared to 145 ps (black) and 263 ps (Teflon) for 20 mm length.